Differential Diagnosis Value of Shear-Wave Elastography for Superficial Enlarged Lymph Nodes - Sun, Yanjuan; Wang, Wen; Mi, Chengrong; Zhang, Qian; Zhang, Kun (Frontiers in Oncology, 2022)
Objectives: To evaluate the diagnostic efficiency and diagnostic threshold of conventional US and shear-wave elastography (SWE) in superficial enlarged lymph nodes (LNs). Methods: A total of 204 patients with superficial enlarged LNs were enrolled in this retrospective study aged at 46.0±15.2 years from March 2020 to March 2021. LNs with long axis larger than 0.7 cm were considered as superficial enlarged. Before histological biopsy, LNs that were considered suspicious according to both conventional US and SWE were included, while LNs with no or unclear pathological results, or with no satisfactory SWE images were excluded. The conventional and 2-D SWE examinations were performed with Aplio i800 and Acuson sequoia equipped with i18LX5 linear-array transducer (5-18 MHz) and 10L4 linear-array transducer (4-10 MHz), respectively. Both E Median and Vs Median parameters were investigated by two senior ultrasound physicians. The pathological results were performed as the gold standard. Results: Variables including transverse axis size, lymphatic hilum, L/T ratio, echogenicity, and color Doppler pattern were considered significance. The mean E Median value in benign, metastatic LNs and lymphoma were 28.26±8.87 kPa, 77.46±22.85 kPa, and 50.37±5.41 kPa (p <0.001), while Vs Median values were 3.02±0.50 m/s, 4.87±0.90 m/s, and 4.09±0.22 m/s, respectively (p < 0.001). The diagnostic performance indicated the high sensitivity, specificity, PPV, NPV and overall accuracy of conventional US combined with SWE. The optimal cutoff values of E Median and Vs Median for predicting malignant LNs were 42.90 kPa and 3.73 m/s, respectively. As AUC value, sensitivity, specificity, accuracy, PPV and NPV revealed, the indexes of E Median were 0.976, 0.927, 0.975, 0.946, 0.983 and 0.897, respectively, while Vs Median were 0.970, 0.927, 0.963, 0.941, 0.975 and 0.895, respectively (p <0.001). The ROC curves of both E Median (AUC=0.976) Vs Median (AUC=0.967) suggested the remarkable diagnostic efficiency in distinguishing benignity between suspected malignant LNs. Conclusions: Above results indicated that conventional US together with 2-D SWE could elevate the diagnostic performance. Meanwhile, the parameters of 2-D SWE including E Median and Vs Median could effectively assess malignant LNs, which provide valuable differentiating information in superficial enlarged LNs.